Densider the arithmetic sequence: \( -\frac{7}{2} ;-3 ;-\frac{5}{2} \ldots \) 1.1 The sum of the first \( n \) terms of this sequence is 675 . Calculate the value of \( n \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the problem, we first need to find the common difference of the arithmetic sequence. The first term \( a_1 = -\frac{7}{2} \) and the second term \( a_2 = -3 \). The common difference \( d \) is calculated as follows: \[ d = a_2 - a_1 = -3 - \left(-\frac{7}{2}\right) = -3 + \frac{7}{2} = \frac{-6 + 7}{2} = \frac{1}{2} \] Now that we have \( d = \frac{1}{2} \), we can find the formula for the \( n \)-th term of the sequence, given by: \[ a_n = a_1 + (n-1)d = -\frac{7}{2} + (n-1)\frac{1}{2} \] This can be simplified to: \[ a_n = -\frac{7}{2} + \frac{n-1}{2} = \frac{-7 + n - 1}{2} = \frac{n - 8}{2} \] The sum of the first \( n \) terms of an arithmetic sequence (denoted as \( S_n \)) is given by: \[ S_n = \frac{n}{2} \cdot (a_1 + a_n) \] Substituting the expressions for \( a_1 \) and \( a_n \): \[ S_n = \frac{n}{2} \left(-\frac{7}{2} + \frac{n-8}{2}\right) = \frac{n}{2} \left(\frac{-7 + n - 8}{2}\right) = \frac{n}{2} \cdot \frac{n - 15}{2} = \frac{n(n - 15)}{4} \] We know that \( S_n = 675 \), so we set up the equation: \[ \frac{n(n - 15)}{4} = 675 \] Multiplying both sides by 4 to eliminate the fraction: \[ n(n - 15) = 2700 \] Rearranging gives us a standard quadratic equation: \[ n^2 - 15n - 2700 = 0 \] We can now solve this equation using the quadratic formula \( n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 1, b = -15, c = -2700 \): \[ n = \frac{15 \pm \sqrt{(-15)^2 - 4 \cdot 1 \cdot (-2700)}}{2 \cdot 1} \] \[ = \frac{15 \pm \sqrt{225 + 10800}}{2} = \frac{15 \pm \sqrt{11025}}{2} \] Calculating \( \sqrt{11025} = 105 \): \[ n = \frac{15 \pm 105}{2} \] This yields two possible solutions: 1. \( n = \frac{120}{2} = 60 \) 2. \( n = \frac{-90}{2} = -45 \) (not a valid solution since \( n \) must be positive) Thus, the value of \( n \) is: \[ \boxed{60} \]